ERS International Congress 2017: preview of the “innovation in diagnosing and monitoring respiratory disease” symposium from the allied respiratory professionals assembly - De Brandt, Jana; Smith, Laurie (Journal of Thoracic Disease; Vol 9, No 12 (December 29, 2017): Journal of Thoracic Disease, 2017)
The symposium on “innovation in diagnosing and monitoring respiratory disease” was organised by ERS group Assembly 9, which represents allied respiratory professionals (lung function technologists, physiotherapists and nurses), at the ERS International Conference in Milan [Session 542, Wednesday 13th of September at Beige (South) room from 10:45–12:45].